Reverse Sural Artery Flap – A Versatile Option in Distal Lower-limb Reconstruction - Om Prakash; Sheikh Sarfraz Ali; Mohammed Fahud Khurram; Mohd. Yaseen (Journal of Orthopedics, Traumatology and Rehabilitation)
Background: The biggest barriers to the reconstruction of soft-tissue defect in the distal part of the lower limb are the paucity of local vascularized soft tissue and the mechanical demands of the region. Advancements in microsurgery techniques and low complication rates have made free tissue transfer the method of choice. However, the option of microsurgery may not be available at all centers. The reverse sural artery flap (RSAF) provides a reliable alternative for covering soft-tissue defects of the distal parts of the lower extremity. Objective: The aim of this study was to assess the versatility and efficacy of RSAF for providing coverage for soft-tissue defects over the distal parts of the lower limb. Materials and Methods: A retrospective, observational, and descriptive study was performed through a data survey of medical records of patients treated between August 2020 and January 2023. Results: A total of 25 patients underwent surgery, 21 males and 4 females. The age range of patients was from 18 to 55 years. Tissue defects following trauma constituted majority of the cases. Four patients had partial flap necrosis. No case of total necrosis of flap was recorded. The average duration of hospital stay was 15.6 days. Conclusion: The reverse-flow fasciocutaneous sural flap proved to be a feasible, easily reproducible, and reliable option for reconstruction of distal lower-limb defects.